Synergistic Antifungal Effect of Fluconazole Combined with Licofelone against Resistant Candida albicans - Liu, Xinning; Li, Tao; Wang, Decai; Yang, Yilei; Sun, Wenwen; Liu, Jianqiao; Sun, Shujuan (Frontiers in Microbiology, 2017)
Candida albicans (C. albicans) is one of the important opportunistic fungal pathogens that is closely associated with disseminated or chronic infections. The objective of this study is to evaluate the synergistic antifungal effect of licofelone, which is dual microsomal prostaglandin E2 synthase/lipoxygenase (mPGES-1/LOX) inhibitor in combination with fluconazole against C. albicans. Here our results showed that licofelone (16μg/mL) can synergistically work with fluconazole (1μg/mL) against planktonic cells of fluconazole-resistant C. albicans. The two-drug combination inhibited the C. albicans biofilm formation over 12 h, and reduced the expression of extracellular phospholipase genes, biofilm-specific genes and RAS/cAMP/PKA pathway related genes. In addition, the two-drug combination inhibited the transition from yeast to hyphal growth form, and decreased the secreted aspartyl proteinase activity, while not affecting the drug efflux pumps activity. Galleria mellonella model was also used to confirm the antifungal activity of the drug combination in vivo. This study first indicates that the combination of fluconazole and licofelone has synergistic effect against resistant C. albicans and could be a promising therapeutic strategy for the antifungal treatment.